Ajaran Satvika Yadnya Sebagai Konsep Pendidikan Menuju Kesejahteraan Umat Dalam Beragama Sosial - Anak Agung Gde Krisna Paramita (Kamaya: Jurnal Ilmu Agama, 2021)
The practice of social religion, which is an agreed dimension, is a noble culture, as a visualization of a form of religious education in the community (non-formal). Humans as the main actors, can not be separated from departing from full faith, have nuances of sincere sincerity in their application. In the Hindu perspective the name satvika yadnya with its teachings dominates on the path through devotion and karma as the main basis. In this research, he succeeded in finding the teaching that satvika yadnya as a trajectory of social education in Hindu practice, with the manifestation of, "longing to meet God", "longing to realize the visualization of God", "realizing offerings to God" and the application of the teachings of catur kerti (Widhi Kerti, Buda kerti, Manusa kerti, jagad kerti).